Research progress on application of digital health interventions in patients with cutaneous ureterostomy (数字健康干预在输尿管皮肤造口患者中的应用进展) - JI Xuebi (吉学碧); WANG Jun (王俊); WANG Ping (王萍); YE Yingao (叶迎奥); WANG Haifeng (王海峰) (中西医结合护理)
In the context of radical surgical interventions for bladder cancer, ureterodermostomy has emerged as a relatively safe procedure, characterized by reduced invasiveness, rapid postoperative recovery, and a favorable survival rate. Nevertheless, it is imperative to acknowledge that permanence and lack of control associated with ureteral dermatostomy may precipitate a myriad of physiological and psychological challenges postoperatively. Concurrently, the accelerated advancement of mobile technology and information systems has led to the integration of digital health interventions, which significantly enhance the convenience for these patients, thereby elevating their quality of life and providing assistance. This paper reviews studies on concepts and related policies of digital health, and current status of clinical application of digital health interventions in patients with cutaneous ureterostomy. Recommendations for future development were discussed with the aim of informing the future promotion and development of digital health interventions in China. (输尿管皮肤造口术是膀胱癌患者常用治疗术式, 具有安全性高根、创伤小、恢复快等优势。输尿管皮肤造口是永久性的, 术后需要长期的护理管理。随着移动设备和信息技术的快速发展, 数字健康干预在提高患者的生活质量、助力患者症状和症管理、改善患者焦虑状态方面展现出显著的优势。本研究就数字健康干预的概念及相关政策、数字健康干预在输尿管皮肤造口患者中的应用现状进行综述, 并对未来发展提出建议, 旨在为我国今后数字健康干预的推广和发展提供参考。)